Open innovation across the prosperity gap: An essay on getting the Caucasus back into the European innovation society - Steffen Roth (IBSU Scientific Journal (IBSUSJ), 2008)
The paper shows how both intra-national and international strategies of open innovation and crowdsourcing could be used to reduce or even invert the brain drain of Caucasian societies, leading to more sustainable and, above all, local returns on investment in the region s excellent educational infrastructure.
Keywords: 330; open innovation; crowdsourcing; brain drain; brain gain; Caucasus; innovation competition; Diaspora networks; regional development